Patients with ocular toxocariosis seen in Hospital Nacional Cayetano Heredia, Hospital Nacional Arzobispo Loayza, and the Instituto Nacional del Niño between 1997 and 2010 - Ramírez Bustamante, Claudia Elena (2010)
Objective: To describe clinical, image, and laboratory findings in patients with eye toxocariasis seen in three of the main ophthalmology services in three national hospitals in Lima, Peru.   Material and method: records of patients with a presumptive diagnosis of ocular toxocariosis between January 1997 and January 2010 in Cayetano Heredia National Hospital, Arzobispo Loayza National Hospital and the Instituto Nacional de Salud del Niño (national reference center for sick children).   Results: Forty-one cases were found. Their ages were between 5 moths and 62 years (11.6 ± 8). The most frequent symptom was reduced visual acuity. Most frequent findings in eye funduscopy and image studies were peripheral granulomata and posterior uveitis.Most patients had positive serology tests for Toxocara canis.   Conclusions: Most patients in this review ere children and adolescents, and some of them developed variable degrees of visual impairment secondary to ocular toxocariosis.